Infection on the meshes implantation area in the abdominal wall of rats with induced bacterial peritonitis - Sebben,Geraldo Alberto (2006)
PURPOSE: Evaluate incidence of bacterial growth on implanted meshes in the abdominal wall of rats after to induce bacterial peritonitis. METHODS: 36 rats were used. They were allocated in two groups: group B, experiment group (n =18) and group S, control group (n =18). They were submitted to the implant of polypropylene meshes on the abdominal wall, at the preperitoneal space. Then, in the animals of the experiment group, the induction of peritonitis was made through the inoculation in the peritoneal cavity of standardized solution of Escherichia coli. In the animals of the control group it was made through the inoculation of physiologic solution. The animals of both groups were reallocated in three subgroups of six animals and observed until the reoperations time, for evaluation of the implantation sites, collection of the meshes for cultures, evaluation of the abdominal cavity and peritoneal lavage for cultures. The reoperations occurred in 24, 48 and 72 hours. RESULTS: All the animals of the experiment group presented clinical symptoms of peritonitis. The cultures of the meshes taken off from the implantation sites were positive in 83% of the animals when the moment of the evaluations was of 24 hours, decreasing to 33% in 48 hours and 17% in 72 hours. Globally, it was of 44%. In the animals of the control group there was no case of positive culture neither in the meshes, nor in the peritoneal lavages. CONCLUSIONS: The experimental model used was effective, producing 100% of peritonitis. The incidence of bacterial growth on the implanted polypropylene meshes was 83% in 24 hours, decreasing with the time.